Es útil la gestión de los recursos humanos en los ayuntamientos? - María Isabel Barba Aragón; José Serrano Segura (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2015)
– Is human resource management in local councils useful? In the current crisis, is the expenditure in this area justified? Although investment in human resources management has been widely studied at the private enterprise, research is scarce in the area of Spanish public administration. To fill this gap, this work carried out a study on a sample of 85 Spanish municipalities of more than 20,000 inhabitants. Analysis supports the idea that actually some practices of human resources have positive effect on the results of local corporations. In fact, although there are practices that are very regulated by the public service regulations you can manage more efficiently without colliding with the law in force.
Keywords: M12; M50; 330; Human resource practices; Public administration; Local councils; Results